(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Mobile devices are among the most common new technologies of the year, gaining even more spread over and success in the day-to-day life of wide range of people. Unfortunately, while the number of mobile devices are used in crime activities is spreading and growing all over the world, the capability to perform the forensics analysis of such devices is limited both by technological and methodological problems. In this paper, we focus on anti forensics techniques applied to mobile device. Furthermore we observe the effectiveness of techniques.Â